A Freezing‐Induced Turn‐On Imaging Modality for Real‐Time Monitoring of Cancer Cells in Cryosurgery. Issue 12 (14th February 2019) - He, Zhiyuan; Liu, Pai; Zhang, Shizhong; Yan, Jie; Wang, Mengni; Cai, Zhengxu; Wang, Jianjun; Dong, Yuping
Abstract: Cryosurgery has attracted much attention for the treatment of tumors owing to its clear advantages. However, determining the volume of frozen tissues in real‐time remains a challenge, which greatly lowers the therapeutic efficacy of cryosurgery and hinders its broad application for the treatment of cancers. Herein, we report a freezing‐induced turn‐on strategy for the selective real‐time imaging of frozen cancer cells. As a type of aggregation‐induced emission (AIE) fluorogen, TABD‐Py molecules interact specifically with ice crystals and form aggregates at the ice/water interface. Consequently, bright fluorescent emission appears upon freezing. TABD‐Py molecules are enriched mostly in the cancer cells and exhibit high biocompatibility as well as low cytotoxicity; therefore, a freezing‐induced turn‐on imaging modality for cryosurgery is developed, which will certainly maximize the therapeutic efficacy of cryosurgery in treating tumors. Abstract : Blue ice : TABD‐Py was used to develop a freezing‐induced turn‐on imaging modality for cryosurgery. A type of aggregation‐induced emission (AIE) fluorogen, TABD‐Py molecules interact specifically with ice crystals and form aggregates at the ice/water interface, resulting in bright fluorescent emission upon freezing.